From impunity to accountability of perpetrators of internal conflicts in Nigeria: Lessons from foreign jurisdictions - Ekpa, Shedrack; Md Dahlan, Nuarrual Hilal (Sweet & Maxwell Asia, 2016)
Over the years, Nigeria has been inundated with recurring internal violence owing to impunity exacerbated by absence of robust measures towards ensuring that culprits are made to bear responsibility for their involvement in internal armed conflicts.These phenomena of incessant violence have left behind harrowing tales on Nigeria with colossal human and capital losses. This article being a conceptual analysis investigates this emerging issue in the light of the standards set in the normative framework for Internally Displaced Persons (IDPs) and the extent of its application in Nigeria relying on primary and secondary sources.This study also delves into an exploration of laws and practices in other foreign jurisdictions insofar as this subject is concerned.At the end of the day it finds inter alia that unless proactive legal and institutional measures are swiftly taken by Nigerian Government, this atmosphere of brazen impunity will continue to thrive and thus the problems arising therefrom such as incalculable deaths, wanton destruction of properties and internal displacement and the likes will continue to confront the nation.This research is significant on the ground that the relative findings and recommendations will go along away to curb the increasing menace of incessant violence in Nigeria through effective penal sanctions and restorative measures in ameliorating the attendant challenges.